Pengaruh Profitabilitas, Leverage, Ukuran Perusahan dan Kebijakan Dividen Terhadap Return Saham pada Perusahaan Sektor Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia - Mita Yuli Cahyati; Sri Hermuningsih; Ratih Kusumawardhani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Stock returns are one of the reasons why someone is interested in investing in stocks in the capital market. This study was conducted to determine the effect of profitability, leverage, company size and dividend policy on stock returns of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique was carried out by purposive sampling method in order to obtain a sample of 17 companies. The results showed that the profitability variable as measured by ROA had a positive and significant effect on stock returns. Leverage is measured by DER and the Firm Size variable has no effect on stock returns. Dividend policy measured by the DPR has a negative and significant effect on stock returns.